2020
DOI: 10.1007/s12028-020-00969-5
|View full text |Cite
|
Sign up to set email alerts
|

Tidal Volume Lowering by Instrumental Dead Space Reduction in Brain-Injured ARDS Patients: Effects on Respiratory Mechanics, Gas Exchange, and Cerebral Hemodynamics

Abstract: Background: Limiting tidal volume (V T), plateau pressure, and driving pressure is essential during the acute respiratory distress syndrome (ARDS), but may be challenging when brain injury coexists due to the risk of hypercapnia. Because lowering dead space enhances CO 2 clearance, we conducted a study to determine whether and to what extent replacing heat and moisture exchangers (HME) with heated humidifiers (HH) facilitate safe V T lowering in braininjured patients with ARDS. Methods: Brain-injured patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…In a prospective observational study of 11 ARDS patients with hypercapnia, the removal of HME (dead space of 100 mL) reduced PaCO 2 levels by 11 ± 5 mm Hg [7] . Subsequently, a prospective study of a small number of ARDS patients reported that the removal of HME significantly improved hypercapnia, confirming the usefulness of this intervention [12–14] . Moreover, in some of these studies, it was possible to achieve lung-protective ventilation by improving hypercapnia [13,14] .…”
Section: Discussionmentioning
confidence: 88%
“…In a prospective observational study of 11 ARDS patients with hypercapnia, the removal of HME (dead space of 100 mL) reduced PaCO 2 levels by 11 ± 5 mm Hg [7] . Subsequently, a prospective study of a small number of ARDS patients reported that the removal of HME significantly improved hypercapnia, confirming the usefulness of this intervention [12–14] . Moreover, in some of these studies, it was possible to achieve lung-protective ventilation by improving hypercapnia [13,14] .…”
Section: Discussionmentioning
confidence: 88%
“…In the present study, ICCI was significantly more present among patients with obesity. CHD prevalence was not different between groups, probably because our entire sample was composed by SARS patients, included in early stages of respiratory function depression and mechanical ventilation support, when CHD is commonly observed 31 . Survival and mechanical ventilatory support successful weaning were also significantly higher among non‐obese subjects.…”
Section: Discussionmentioning
confidence: 92%
“…An adequate oxygen supply to the organs is essential for an organism to be able to function normally. 8,[36][37][38] It is known that interruption of the oxygen supply for just 5 min can cause irreversible brain damage in humans. 9 Blockage of blood flow by thrombosis in ischemic stroke dramatically decreases the oxygen supply to the area distal to the thrombus.…”
Section: Discussionmentioning
confidence: 99%